Ozone water or chloroxylenol: The comparison of disinfection effectiveness against the number of bacterial colonies in dental extraction instruments at the Universitas Sumatera Utara Dental and Oral Hospital [version 4; peer review: 1 approved, 2 approved with reservations, 1 not approved] - Ahyar Riza; Ismahani Akilah D; Rahmi Syaflida Dalimunthe; Hendry Rusdy (F1000Research)
Background The application of disinfectants on dental instruments is one way to prevent cross-infection. The urgency in this research is ozone water as a disinfectant is still limited and no research has been found on the use of ozone water on tooth extraction instruments. However, ozone has antibacterial properties so researchers are interested in studying the effectiveness of ozone water as a disinfectant when compared to the commonly used 4.8% chloroxylenol. This study aimed to determine the effectiveness of disinfection of ozone water and 4.8% chloroxylenol in reducing the number of bacterial colonies on dental extraction instruments at the Universitas Sumatera Utara Dental and Oral Hospital. Methods The samples used were mandibular molar forceps have been used in tooth extraction procedures. This study was experimental and used 30 sample, where each group consisted of 10 tooth extraction instruments. The treatment group used ozone water and 4.8% chloroxylenol and the negative control group was cleaned with distilled water. The ozone water group was produced with an ozone generator with a concentration of 15 mg/L for 20 minutes. Then the active side of tooth extraction forceps was soaked for 30 minutes. In the 4.8% chloroxylenol (dettol®️) group, the active side of the mandibular molar tooth extraction forceps was soaked in 250 mL for 60 minutes. In the control group, the mandibular molar tooth extraction forceps were rinsed with distilled water. After that, the sample was counted using a bactery colony counter. Results The results of the data analysis showed a p-value ≤0.001, which means there was a significant difference in the disinfection using ozone water and 4.8% chloroxylenol on the number of bacterial colonies on dental extraction instruments. Conclusions From this study it can be said that ozone water is more effective in disinfecting than 4.8% chloroxylenol.